Comportamiento de una sola aplicación de Aldrin, Dieldrin y Heptachlor en el combate del gusano blanco, Barotheus castaneus (Er.) en dos cultivos consecutivos de papa en Ecuador - Merino M., Gualberto; Vasquez, Victor (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
Potatoe crops of the Ecuadorean bigblands are mostly affected by insect soil Pests Larrde of Barotheus castaneus (Ex) injure up to 65 percent of the hish potatou tubers besides of the damage caused to the roots In order to determine its chemical control, a field test was conducted at Palmiva, Chimborazo province, from November 1959 to July 1961, under a factorial split-plot design 3x3x2, evaluating Aldvin, Dieldrin and Heptachlon at the rates of 5 and 75 pounds of active ingredient per bectare, with two systems of application to the rou's and to the entire soil surface. Results were measured in terms of larvae population at the first and second harvest at 8 and 20 months after the first and unique spray Global results involving both countings indicate that the three insecticides achieve an efficient control up to the 20 months. Aldvin is equally effective than Dieldrin with both being slightly better than Heptachlor Five and 75 pounds show's no significant differences but are highly sig-nificantly better than the check The funou's application are slightly more effective than the entire soil toface system, in spite of for the second planting the row's application system dessapeared because the pre-planting soil preparation The com-parisons between the partial results obtained at 8 and 20 months, indicate that the insecticides the tuo dosages and systems acbiete approximately equal effectiteness with Heptachlon and the furrou's application system being slightly better up to the S months than to the 20.